A Medium-Term Macroeconomic Strategy for Algeria : Sustaining Faster Growth with Economic and Social Stability, Volume 1. Main Report - World Bank (Washington, DC, 2013)
This study is part of a series of analytical works on Algeria prepared by the Bank, with the aim of laying out the framework, and facilitating the dialogue for elaborating the Bank's Country Assistance Strategy for Algeria. Companion studies include: "A Private Sector Development Strategy Note: A Diagnostic on Foreign Direct Investment in Algeria" (FIAS). This report is divided into three parts. It presents a diagnostic of the slow growth performance, by benchmarking Algeria's performance against other comparator countries, with the aim of identifying the key bottlenecks to better long-term growth performance in Algeria". Building on this analysis, experience from transition economies, and diagnostics in the companion reports, the second part reviews options in structural reforms to encourage the development of the private sector, by strengthening the investment climate and furthering Algeria's transition to the market. the third part examines options to strengthen the fiscal framework, to insulate the fiscal stance from volatile hydrocarbon fiscal revenues and secure fiscal sustainability, so as to achieve a sustained acceleration of growth. More technical background material of the analysis is presented in the annexes, in volume two.